Quantifying single gene copy number by measuring fluorescent probe lengths on combed genomic DNA - Herrick, John (The National Academy of Sciences, 2000)
An approach was developed for the quantification of subtle gains and losses of genomic DNA. The approach relies on a process called molecular combing. Molecular combing consists of the extension and alignment of purified molecules of genomic DNA on a glass coverslip. It has the advantage that a large number of genomes can be combed per coverslip, which allows for a statistically adequate number of measurements to be made on the combed DNA. Consequently, a high-resolution approach to mapping and quantifying genomic alterations is possible. The approach consists of applying fluorescence hybridization to the combed DNA by using probes to identify the amplified region. Measurements then are made on the linear hybridization signals to ascertain the region's exact size. The reliability of the approach first was tested for low copy number amplifications by determining the copy number of chromosome 21 in a normal and trisomy 21 cell line. It then was tested for high copy number amplifications by quantifying the copy number of an oncogene amplified in the tumor cell line GTL-16. These results demonstrate that a wide range of amplifications can be accurately and reliably quantified. The sensitivity and resolution of the approach likewise was assessed by determining the copy number of a single allele (160 kb) alteration.